Effect of Heat Treatment of Broken Rice Flour as Partial Substitution of Wheat Flour on the Qualities of Bread - Khwanchai, Paidaeng; Fong-In, Suwalee (Burapha Science Journal, 2026)
The effects of heat treatment on broken rice flour functionality in produced bread by partial substitution of wheat flour were investigated. The broken rice flour was subjected to dry-heat by hot air oven at two temperatures (90 °C and 120 °C) for 1, 2, and 3 hr. The physicochemical and sensory properties of heat-treated, substituted broken rice flour bread were studied and compared with control of non-heated, substituted broken rice flour bread and wheat flour bread. The heat-treated broken rice flour bread was more considerably obtained in moisture content than the non-heated broken rice flour bread. Heating the broken rice flour at 120 ºC for 2 hr produced bread with the highest specific volume (2.80 cm3/g) and no significant difference in springiness (p>0.05) was obtained when compared with wheat flour bread. The control non-heated broken rice flour bread produced breads with low volume, a weaker crumb structure which collapsed, and lower springiness. Additionally, bread made from this heat treatment of broken rice flour was more acceptable than the non-heat flour in consumer testing. The overall acceptability score for bread made with heat treated rice flour at 120 ºC for 2 hr was 6.67 compared to 4.43 for non-heated broken rice flour bread. Thus, heating the broken rice flour at 120 ºC for 2 hr enhanced in overall volume, cell structure, texture and overall consumer acceptance of bread. In conclusion, these results can assist in improving the quality of partial substitution of wheat flour with rice flour in baking products for consumers. Furthermore, it can be developed the other bakery products with partial substitution of wheat flour with other plants flour for selling on the health-conscious market in the future.